Dynamics of ultrafast laser introduced breakdown in water and ethanol - Su, Lan; Qiu, Xin; Guo, Rui; Jing, Youbo; Yang, Chaosan; Liu, Shuhui (Frontiers in Physics, 2025)
Femtosecond laser with pulse duration of 35 fs is used to introduce optical breakdown in water and ethanol. The initial dynamics of the laser-introduced break down is investigated with a time resolved shadow imaging method. The motion of the shock wave front at 600 ps, 4 ns, 12 ns, 16 ns, and 20 ns are observed. Experimental results indicate that under the same laser energy, the initial velocity of the shock wave generated in ethanol is slightly lower than that in water. This is mainly determined by liquid properties (viscosity coefficient, density, molecular weight, breakdown threshold). The evolution of the shock wave also indicates that the velocity decreases with time, and the decrease in ethanol is faster than that in water.